Determinants of Bone Strength Estimated by Calcaneal Ultrasonography in Inuit Women from Nuuk (Greenland). (26th March 2014) - Paunescu, Alexandra-Cristina; Ayotte, Pierre; Dodin, Sylvie; Dewailly, Éric; Mulvad, Gert; Pedersen, Henning S.; Côté, Suzanne
Abstract : This study was conducted to identify determinants of bone strength estimated by quantitative ultrasonography (QUS) at the calcaneus of Greenlandic Inuit women. A total of 153 Inuit women from Nuuk, aged from 49 to 64 years, participated in the first QUS measurement (year 2000) with an Achilles Lunar instrument (speed of sound (SOS); broadband ultrasound attenuation (BUA); stiffness index (SI)). A second measurement was performed two years later (year 2002) in 121 participants. Several factors known to be associated with bone strength were recorded at baseline for 118 of them. Determinants of QUS parameters were identified using an automatic (stepwise) selection of variables in linear regression. Significant determinants of baseline QUS measurements were age and body weight for all QUS parameters, height for BUA and SI, and hormone replacement therapy (HRT) use for SI. Significant predictors of follow-up QUS measurements were baseline QUS values, the smoking status and HRT use for all QUS parameters, omega-3/omega-6 PUFA content ratio of erythrocytes membrane phospholipids (BUA and SI), and menopausal status (BUA). Several modifiable dietary factors, such as a diet rich in omega-3 PUFAs and lifestyle factors (i.e., smoking, taking HRT), were shown to determine QUS parameters after a follow-up of two years.